(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to find out which impacted mandibular third molar (3M) positions or bone morphology types at the 3M site could lead to the potential risk of accidental displacement of 3M root fragments into the sublingual soft tissues. Materials and Methods: The sample consisted of 103 patients with an impacted mandibular 3M (vertical, mesioangular, or horizontal position) seen on at least one side using cone beam computed tomography images. The bone morphology at the 3M sites were classified as round shape, lingual concavity, and lingual extended. The relationship between the roots and the sublingual soft tissues was classified as: 1) type A, in which some amount of bone appears between the root and the soft tissues; 2) type B, in which the root apex is located at the lingual cortical plate; and 3) type C, in which the root apex has penetrated into the soft tissues. Results: Binary logistic regression analysis showed that the odds of lingual extended bone morphology are 2.61 times greater for potential root displacement in combined types B and C, compared to round shape. Conclusion: These results suggest that impacted mandibular 3Ms with the lingual extended morphology type are more likely to cause root fragment displacement into the sublingual soft tissues. Keywords: Third molar; mandible; cone beam computed tomography; iatrogenic displacement; sublingual space.